Cloning the gene for an inherited human disorder--chronic granulomatous disease--on the basis of its chromosomal location. - Royer-Pokora, B; Kunkel, L; Monaco, A; Goff, S; Newburger, P; Baehner, R; Cole, F; Curnutte, J; Orkin, S (1986)
The gene that is abnormal in the X-linked form of the phagocytic disorder chronic granulomatous disease has been cloned without reference to a specific protein by relying on its chromosomal map position. The transcript of the gene is expressed in the phagocytic lineage of haematopoietic cells and is absent or structurally abnormal in four patients with the disorder. The nucleotide sequence of complementary DNA clones predicts a polypeptide of at least 468 amino acids with no homology to proteins described previously.